Konsep Penelitian Kualitatif : Tinjauan Pustaka, Studi Kasus, Pendekatan Etnografi, Informan, In-Depth Interview dan Focus Group Discussion - Primadi Candra Susanto; Josua Panatap Soehaditama; Atong Soekirman; Agus Suhendra; Adelia Dwi Valentin; Sismiati Sismiati (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
The purpose of this literature study is to develop a hypothesis regarding the influence between variables that can be used for further research in the scope of research methodology. Literature review research articles on qualitative research concepts: literature review, case studies, ethnographic approaches, informants, in-depth interviews and focus group discussions are scientific literature articles in the scope of research methodology. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use a literature study or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and is sourced from academic online media such as Thomson Reuters, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Literature Review plays a role in the Concept of Qualitative Research; 2) Case Study plays a role in the Concept of Qualitative Research; 3) Ethnographic Approach plays a role in the Concept of Qualitative Research; 4) Informants play a role in the Concept of Qualitative Research; 5) In Depth Interview plays a role in the Concept of Qualitative Research; and 6) Focus Group Discussion plays a role in the Concept of Qualitative Research.